Decision Making Autonomy and Maternal Healthcare Utilization among Nigerian Women - Phillips Edomwonyi Obasohan, MBA, MEd, MSc; Paul Gana, MSc; Mahmud A. Mustapha, MSc; Ahmed Egbako Umar, PhD; Audu Makada, MSc; Dorcas Nike Obasohan, BSc (Global Health and Education Projects, Inc., 2019)
Background and Objectives: Low assess to ante-natal care (ANC) services continue to pose a major public health challenge leading to high maternal mortality rates in developing countries. Non-utilization of ANC services among about a quarter of Nigerian women of reproductive age remains a major concern in the actualization of Sustainable Development Goals. Considering the complexity of healthcare utilization in Nigeria, the relationship between a particular health care utilization pattern and women autonomy has not been fully examined. This study examines the patterns of women autonomy and their relationships with ANC utilization in Nigeria. Methods: This was a cross-sectional analysis of the 2013 nationally representative data from the Nigerian Demographic and Health Survey (NDHS). Factor analysis/score were used to construct women autonomy index, while chi-square and logistic regression were used to establish the relationships between the response and exposure variables. Results: There is a strong relationship between women decision making autonomy status and ANC services among Nigeria women. The odds of utilizing ANC services among women with more decision making autonomy were significantly 3.79 higher than among women with low decision-making autonomy. The use of ANC increases as age, education and wealth status of respondents increase. Conclusions and Global Health Implications: These results indicate that women autonomy is undoubtedly a major determinant of ANC utilization in Nigeria. Key words: Autonomy, Antenatal Care, Logistic Regression Analysis; Factor analysis   Copyright © 2019 Obasohan et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.affect economic and health promotion.